Moral Disengagement and the Social Construction of Procurement Officers’ Deviant Behaviours - Mpeera Ntayi, Joseph; Eyaa, Sarah; Ngoma, Muhammed (Journal of Management Policy & Practice, 2010)
In this study we attempt to explain the recent unethical practices of public procurement officers in Uganda using Bandura’s (1999) moral disengagement variables and Durkeim’s (1858-1917) notion of anomie. Perceived normative conflict and procurement planning behavior are added to the model to examine their relative effect on the behavior of procurement officers. Using data from 405 usable questionnaires collected from both Central and Local Government the study finds that Moral disengagement, perceived normative conflict, work anomie and procurement planning are significant predictors of social construction of procurement officers’ deviant behaviors. The interactive effect of moral disengagement and procurement planning behaviors diminishes the social construction of procurement officers’ deviant behaviors. These findings have both policy and managerial implication which we later present in the paper.
Keywords: Moral Disengagement; Social Construction; Procurement Officers’ Deviant Behaviours